In the Territory of Uncertainty: Interview, Poems and the Author’s Own Comments - Sánchez Santiago, Tomás (2021)
Interview with the contemporary Spanish poet Tomás Sánchez Santiago, author of a considerable and varied literary work, which includes poetry, narrative, chronicle and essay. The conversation covers a wide range of issues: from the development of a writer to the multiple instances that literary practice faces in contemporary western society. The writer distinguishes between the current social role of literature and the defense of writing, always with an aesthetic will, as a space and awareness of the circumstances of coexistence, regardless of other expectations. Poetry, he maintains, is radicalism, exploration of the senses and commitment to the very essence of the word: unveiling the hidden, disorganizing to achieve another order, another richer and more bearable dimension. Notes and explanatory data from the person who guided the interview are added, as well as a poetic selection and comments by the writer himself.